Lighting Up T Lymphocyte Signaling with Quantitative Phosphoproteomics - Álvarez-Salamero, Candelas; Castillo-González, Raquel; Navarro, María N. (Frontiers in Immunology, 2017)
Phosphorylation is the most abundant post-translational modification, regulating several aspects of protein and cell function. Quantitative phosphoproteomics approaches have expanded the scope of phosphorylation analysis enabling the quantification of changes in thousands of phosphorylation sites simultaneously in two or more conditions. These approaches offer a global view of the impact of cellular perturbations such as extracellular stimuli or gene ablation in intracellular signaling networks. Such great potential also brings on a new challenge: to identify, among the thousands of phosphorylations found in global phosphoproteomics studies, the small subset of site-specific phosphorylations expected to be functionally relevant. This review focus on updating and integrating findings on T lymphocyte signaling generated using global phosphoproteomics approaches, drawing attention on the biological relevance of the obtained data.